Views on EFL Testing System - Avakyan, Naira (Armenian Folia Anglistika, 2010)
The article discusses the two most popular types of tests in the EFL testing system – multiple choice and free response questions. Both of the tests have their advantages and disadvantages. Psychological and fairness-related factors are of significant importance during an exam. The article highlights certain reforms suggested by the author in relation to oral HEI entrance exams.